Can a Mother's Parenting Style Predict Adolescent Oral Hygiene Behavior? A Self-Reported Cross-Sectional Study - Annisa, Deva; Abidin, Fitri Ariyanti; Setiawan, Arlette Suzy (European Journal of Dentistry, 2023)
Objective Adolescent oral hygiene behavior plays a crucial role into adulthood and still requires attention from parents, especially mothers. Parenting done by the mother will directly affect the child's life, including the child's oral hygiene behavior. The aim of this study was to determine the role of the mother's parenting style in predicting adolescent oral hygiene behavior.Materials and Methods A quantitative study with a cross-sectional approach was used to examine the role of parenting style on their teenage child's oral hygiene behavior. The instruments used were (1) a parenting style measuring instrument to measure supportive and nonsupportive parenting styles of mothers (parent as social context questionnaire) and (2) a self-structured oral hygiene behavior measuring instrument based on the theory of planned behavior. The population of this study were students at SMP PGRI Depok and SMP Negeri 11 Depok, West Java, aged between 12 and 14 years. The sampling technique used total sampling on SMP PGRI students and multistage random sampling on students at SMP Negeri 11 Depok with a total sample of 230 students. Data analysis was done using multiple linear regression test.Results Statistical regression tests showed that nonsupportive parenting style did not predict adolescent oral hygiene behavior (p = 0.567), while supportive parenting style did predict adolescent oral hygiene behavior (p = 0.000). Supportive parenting style predicts 31.2% of adolescent oral hygiene behavior.Conclusion Mother's supportive parenting style plays a role in predicting adolescent oral hygiene, and the mother's nonsupportive parenting style does not play a role in predicting adolescent oral hygiene behavior.
Keywords: supportive parenting style; nonsupportive parenting style; oral hygiene behavior; adolescents